WOMEN ON THE NOVELS OF ASMA NADIA (GYNOCRITIC STUDY) - Puspa Indah Utami; Emzir Emzir; Ninuk Lustyantie (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The objectives of the research were three novels of Asma Nadia which discussed the issue of women. The novels are Surga yang tak dirindukan, Asslamualaikum Beijing, Cinta 2 Kodi. This research used qualitative approach with content analysis method using gynocritic study. The data of this research was obtained through the reading of the novel repeatedly and intensively, identifying, recording, classifying, and testing the validity of the data through credibility, transferability, dependability, and confirmability. The issues discussed in this research related to Novel Structure and Biology of Women. The findings of this research is recommended in practice for the next researchers who will complete the study of the other side, and to the lectures who want to teach literature, especially the works of literary novels.